(untitled) (Global Journal of Computer Science and Technology, 2014)
COTS based development is becoming a popular software development approach for building large organizational software using existing developed components. COTS based approach provides pre-developed components either as in house or commercial off the shelf components, which reduces effort and cost for developing the software. There are potential challenges, risks and complexities in using COTS components. This paper provides an analysis of risks and challenges faced during developing software using CBSD approach. The risks under various phases are identified, categorized and prioritized the risks in various phases of CBSD and provide the mitigation strategy to manage the risks.